Frank Knox papers - Knox, Frank, 1874-1944.; Knox, Annie Reid, 1876-1958.
Correspondence, diaries, speeches, writings, newspaper clippings, scrapbooks, and other papers relating to Knox's service as a private in the U.S. Army 1st Volunteer Cavalry (Rough Riders) during the Spanish-American War and as an artillery officer during World War I, his work as editor and publisher of the Chicago Daily News, his 1936 Republican vice-presidential campaign, and his service as U.S. secretary of the navy (1940-1944). Correspondents include Chiang Kai-shek, Calvin Coolidge, Henry Ford, James Forrestal, Felix Frankfurter, Cordell Hull, Harold L. Ickes, Walter Lippmann, George C. Marshall, John Adam Muehling, Franklin D. Roosevelt, Theodore Roosevelt, Arthur H. Vandenberg, William Allen White, and Wendell L. Willkie. Includes papers (1936-1954) of Knox's wife, Annie Reid Knox.
Library of Congress Prints and Photographs Division.
U.S. secretary of the navy, U.S. Army officer, and newspaper editor and publisher.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Chiang, Kai-shek, -- 1887-1975 -- Correspondence; Coolidge, Calvin, -- 1872-1933 -- Correspondence; Ford, Henry, -- 1863-1947 -- Correspondence; Forrestal, -- James, 1892-1949 -- Correspondence; Frankfurter, Felix, -- 1882-1965 -- Correspondence; Hull, Cordell, -- 1871-1955 -- Correspondence; Ickes, Harold L. -- 1874-1952 -- Correspondence; Lippmann, Walter, -- 1889-1974 -- Correspondence; Marshall, George C. -- 1880-1959 -- Correspondence; Muehling, John Adam, -- 1862-1944 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Vandenberg, Arthur H. -- 1884-1951 -- Correspondence; White, William Allen, -- 1868-1944 -- Correspondence; Willkie, Wendell L. -- 1892-1944 -- Correspondence; United States. -- Army. -- Volunteer Cavalry, 1st.; United States. -- Navy Department; Republican Party (U.S. : 1854- ); Chicago Daily News; American newspapers -- Illinois -- Chicago; Spanish-American War, 1898.; World War, 1914-1918.; Vice-Presidential candidates -- United States -- 1936.; United States -- Politics and government -- 1901-1953.; Cabinet officers; Newspaper editors; Publishers